Analysis on the thermal behaviour of the latent heat storage system using S-CO2 and H-PCM. (May 2023) - Zhu, Ming; Nan, Wenguang; Wang, Yueshe
Abstract: Energy storage and utilization of CO2 have attracted increasing attention due to international zero carbon plan. Here, the latent heat storage system using high-temperature phase change material (H-PCM) and supercritical CO2 (S-CO2 ) is analysed by using CFD simulation, in which the tube containing S-CO2 is submerged in a tank containing the salt with high melting temperature. A new and combined phase transition model is developed to describe the dynamics of PCM in different phase state, and it is validated against experimental data in literature. The dynamics of natural convection is focused, and its effects on the heat storage system are analysed, including maximum natural convection velocity, phase interface, and melting pattern. The results show that natural convection has a great influence on the melting process of the H-PCM in the charging process. The melting pattern of H-PCM could be contrary between the cases with and without considering natural convection. During the discharging process, natural convection has little effect on the heat transfer of energy release due to its short duration. With the increase of ratio between the S-CO2 tube and H-PCM tank, the strength of the natural convection of melting H-PCM is enhanced, especially the duration of natural convection. Graphical abstract: Image 1